The lubrication effect of hyaluronic acid and chondroitin sulfate on the natural temporomandibular cartilage under torsional fretting wear. (25th February 2014) - Wu, Ting‐ting; Gan, Xue‐qi; Cai, Zhen‐bing; Zhu, Min‐hao; Qiao, Meng‐ting; Yu, Hai‐yang
ABSTRACT The aim of this study is to investigate the lubrication of hyaluronic acid (HA) and chondroitin sulfate (CS) on the condylar cartilage of the temporomandibular joint. The wear behaviour of bovine condyle cartilage was explored against a zirconia ball with different lubrications under torsional fretting mode. The worn cartilage morphologies were observed using scanning electron microscopy and hemotoxylin and eosin staining. The results indicated that HA or CS could significantly lower the friction torque and dissipated energy of fretting interface and reduce the damage of the articular cartilage surface compared to the control (phosphate‐buffered saline). The mixture (HA and CS) could provide better protection for the cartilage layer. Absence of good lubrication in overloading torsional fretting process caused excessive cartilage wear. High concentration and high molecular weight HA or CS acted as good boundary lubricants, and the lubrication effect of their mixture was better due to their synergistic function. Copyright © 2014 John Wiley & Sons, Ltd.